Cystic cervical lymph nodes of papillary thyroid carcinoma, tuberculosis and human papillomavirus positive oropharyngeal squamous cell carcinoma: Comparative CT analysis for their differentiation. Issue 132 (November 2020) - Onoue, Keita; Fujima, Noriyuki; Andreu-Arasa, V. Carlota; N. Setty, Bindu; Qureshi, Muhammad Mustafa; Sakai, Osamu
Highlights: Cystic cervical lymph nodes are important findings when considering the differential diagnosis and are seen in several pathologies. Cystic cervical lymph nodes are seen in papillary thyroid carcinoma, tuberculosis, and HPV-positive oropharyngeal squamous cell carcinoma. Cystic lymph nodes are differentiated by their morphologies, enhancement patterns and presence/absence of calcification. Accurate lymph node differentiation is crucial for diagnosis and staging, particularly when the primary malignancy or history is unknown. Abstract: Purpose: Cervical lymph nodes with cystic changes are an important finding seen with several pathologies including papillary thyroid carcinoma (PTC), tuberculosis (TB) and HPV-positive oropharyngeal squamous cell carcinoma (HPV + OPSCC). In the absence of known primary tumor or conclusive medical history, differentiating among these nodes is difficult. We compared the pathologic nodes of PTC, TB and HPV + OPSCC to identify imaging features useful for their differentiation. Materials and methods: Fifty-five PTC, 58 TB and 51 HPV + OPSCC nodes were selected based on surgical pathology records and suspicious morphological features. These nodes were compared for morphological features: long axis length, nodal shape, nodal location, presence of cystic change, area of cystic change:area of entire node ratio, Hounsfield unit of the cystic component, degree of enhancement, enhancement pattern, presence of calcification, presence of perinodal infiltration, and presence of surrounding inflammatory changes. Results: PTC nodes formed calcifications more frequently and demonstrated greater enhancement ( P < 0.01). TB nodes were characterized by their irregular shape ( P < 0.05), irregular enhancement surrounding the cystic change ( P < 0.01), greater frequencies of perinodal infiltration ( P < 0.01) and surrounding inflammatory changes ( P < 0.01). While no unique features were seen with HPV+OPSCC, they were characterized by the absence of those features that distinguished the other groups: these nodes tended to have smooth, circumscribed margins with no hyperenhancement, calcifications or inflammatory changes. PTC and TB nodes were more frequently identified in the lower neck, while HPV+OPSCC nodes were localized to the upper neck ( P < 0.01). Conclusions: PTC, TB and HPV + OPSCC lymph nodes can be differentiated based on their morphologies and locations.